Horticultural Irrigation Systems and Aquacultural Water Usage: A Perspective for the Use of Aquaponics to Generate a Sustainable Water Footprint - Mark Schoor; Ana Patricia Arenas-Salazar; Benito Parra-Pacheco; Juan Fernando García-Trejo; Irineo Torres-Pacheco; Ramón Gerardo Guevara-González; Enrique Rico-García (Agriculture, 2024)
The expansion of food production is becoming more important due to a rising world population, which is relying on food security on regional and local scales. Intensive food production systems exert a negative impact on the regional ecosystem because of agrochemical pollution and nutrient-rich water discharging into nearby rivers. Furthermore, these systems highly depend on regional water resources, causing water scarcity and soil erosion due to the overexploitation of natural resources in general. The objective of this article is to review the water usage in the two most water-intensive food production systems, agriculture and aquaculture, showing lacking areas like system management and climate change, which must be considered in the implementation of a sustainable water footprint. In addition, the review includes an analysis of the combination of both production systems in aquaponic food production and the possibilities of water saving. There are a variety of analyses related to water usage for crop and aquatic animal production, but in these analyses, there is a lack of information about system management in general, which includes cleaning processes, water substitution, pond removal, water evaporation, and, especially in aquaculture, the water usage required for industrially elaborated fish feed.